Strange translation - investigating ires-mediated and codon non-optimal translation dynamics at the single mRNA level in living cells - Koch, Amanda Lynn, author; Stasevich, Timothy, advisor; Munsky, Brian, committee member; Markus, Steven, committee member; Peersen, Olve, committee member; Wilusz, Jeffrey, committee member (Colorado State University. Libraries, 2021)
With the advent of Nascent Chain Tracking (NCT), a technique used to visualize single-molecule events of translation in living cells, answering detailed questions about how, when, and where translation is occurring in living cells is possible. Since its publishing debut in 2016, NCT has provided a wealth of information about translation initiation and elongation dynamics, subcellular localization, translation site structure, and reaction to stress for both canonical and non-canonical translation in living cells. Here, we slightly modify the NCT assay to quantify translation dynamics when a ribosome is recruited to an mRNA in a non-canonical fashion and when a ribosome encounters codon non-optimal stretches on a transcript. The first step of translation requires a primed ribosome to be recruited to a readied mRNA. Canonically, this recruitment takes place on the 5' cap of an mRNA and is termed cap-dependent initiation. However, some eukaryotic messages and many viral RNAs use an internal ribosome entry site (IRES) to recruit ribosomes and initiate translation in a cap-independent manner. Specifically, viruses use IRES elements to hijack host ribosomes to translate viral proteins and properly propagate in host cells. While well- studied in bulk, the dynamics of IRES-mediated translation remain unexplored at the single-molecule level. Here, we developed a bicistronic biosensor encoding distinct repeat epitopes in two open reading frames (ORFs), one translated from the 5'-cap, the other from the Encephalomyocarditis Virus IRES. When combined with a pair of complementary probes that bind the epitopes co-translationally, the biosensor lights up in different colors depending on which ORF is translated. Using the sensor together with single-molecule tracking and computational modeling, we measured the kinetics of cap- dependent versus IRES-mediated translation in living human cells. We show that bursts of IRES translation are shorter and rarer than bursts of cap translation, although the situation reverses upon stress. Collectively our data support a model for translational regulation primarily driven by transitions between translationally active and inactive RNA states. Once the ribosome has been recruited to the mRNA and a start codon located, the ribosome will begin decoding the mRNA in nucleotide triplets or codons to ultimately create a protein. In some cases, the ribosome encounters a codon that it cannot decode efficiently. The relationship between codons and ribosome efficiency is termed codon optimality. It has been shown that codon non-optimal mRNA are less stable in cells. However, little is known about the effects of codon non-optimality on translation kinetics and overall translation regulation. In an ongoing collaboration with the Rissland group, we use bulk assays and NCT to address unanswered questions about how codon non- optimality leads to translation regulation along with mRNA instability. Thus far, we have evidence to support that translation repression is occurring in codon non-optimal conditions through inhibition of ribosome initiation and slower elongation. Further investigations of exact translation repression mechanisms are ongoing.